How Lipid-Specific T Cells Become Effectors: The Differentiation of iNKT Subsets - Wang, Haiguang; Hogquist, Kristin A. (Frontiers in Immunology, 2018)
In contrast to peptide recognizing T cells, invariant natural killer T (iNKT) cells express a semi-invariant T cell receptor (TCR) that specifically recognizes self- or foreign-lipids presented by CD1d molecules. There are three major functionally distinct effector states for iNKT cells. Owning to these innate-like effector states, iNKT cells have been implicated in early protective immunity against pathogens. Yet growing evidence suggests iNKT cells play a role in tissue homeostasis as well. In this review, we discuss current knowledge about the underlying mechanisms that regulate the effector states of iNKT subsets, with a highlight on the roles of a variety of transcription factors, and describe how each subset influences different facets of thymus homeostasis.